أثر تطبيق أدوات الاتصال الداخلي في تحسين أداء الموارد البشرية دراسة ميدانية بمؤسسة المصبرات الغذائية – نقاوس– الجزائر - بحشاشي, رابح (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة إلى تحديد أثر تطبيق أدوات الاتصال الداخلي في تحسين أداء الموارد البشرية، ومدى مساهمتها في تحقيق الأداء الجيد والمتميز في منظمات الأعمال، مع شرح دور إعتماد التقنيات الحديثة للاتصال في تحسين أداء الموارد البشرية في منظمات الأعمال الجزائرية، وذلك بالتطرق إلى أهم الاستراتيجيات لمنتهجة في هذا المجال، مع محاولة إبراز دور إعتمادها في تحسين وتطور اداء الموارد البشرية، وهذا بإجراء دراسة وصفية وتحليلية لطبيعة الاتصالات الداخلية وعلاقتها بأداء الموارد البشر، ومن ثم تقديم استراتيجية بديلة يعمل بها من اجل تحسين مستوى الأداء في منظمات الأعمال الجزائرية. لقد توصلت الدراسة إلى أن منظمة الأعمال محل الدراسة الميدانية تستخدم وسائل الاتصال حديثة الكترونية بما يحقق لها سرعة في إيصال المعلومات لكل موارد البشرية، وأن إستراتيجية الاتصال الداخلي التي تعتمد على الوسائط الالكتروني تساهم بشكل فعال في نقل المعلومات بين العامل من اجل تنفيذ مهامهم وتحقيق اهداف المنظمة في حينها. The study aims to determine the impact of the application of internal communication tools in improving the performance of human resources, and the extent of their contribution to achieving good and distinguished performance in business organizations. , with an explanation of the role of the adoption of modern communication technologies in the improvement and performance of human resources in Algerian business organizations, addressing the most important strategies of the approach in this area, with a focus on attempt to highlight the role of its adoption in improving and developing the performance of human resources, by conducting a descriptive and analytical study of the nature of internal communication and its relationship to the performance that works in order to improve the level of performance in Algerian professional organizations. The study concluded that the business organization concerned by the case study, uses modern electronic communication means to accelerate the delivery of information to all the personnel of the company, and that the internal communication strategy which depends electronic media effectively contributes to the transfer of information between the worker in order to implement their tasks and achieve the objectives of the organization
The impact of applying internal communication tools on improving human resource performance A field study at the Food Canning Corporation -Naqaous - Algeria
مقال
Keywords: الاتصال الداخلي، إستراتيجية الاتصال، إدارة المروارد البشرية،الاتصال الحديث، منظمة الأعمال; Internal communication ; communication strategy; human resource management; modern communication; business organization ; Keywords: Internal communication ; communication strategy; human resource management; modern communication; business organization.